The Effect of Assessment for Learning Integration in Scientific Approach Towards Students’ Conceptual Understanding on Work and Energy - Nur Elisa; Sentot Kusairi; Sulur Sulur; Ahmad Suryadi (Universitas PGRI Kanjuruhan Malang, 2019)
This study aims to determine the effect of the integrated assessment for Learning (AfL) which is assisted by the Tryout application in scientific approach on students' conceptual understanding. This study used a quasi-experimental method with a pretest-posttest control group design. This research was conducted at a high school in Malang with a sample of two classes by a random cluster sampling technique. There were two classes involved, namely one as an experimental class (using an integrated AfL assisted with a tryout application in scientific approach) and one as a control class (using a scientific approach through assignment instructions). Thirthy four students in each class were tough the work and energy topic. The test instrument used was 20 reasoned multiple-choice questions with a reliability of 0.62. Data were analyzed using descriptive analysis and inferential statistics. The results showed that there was a significant difference between the posttest mean scores of the experimental class students and the control class students (p = 0.017). Descriptive analysis showed that the mean scores of posttest students for the experiment and control class were 61.76 and 54.26, respectively. That means that the conceptual understanding of students who learn with integrated AfL that assisted by tryout application in scientific approach was higher than students who learn with the scientific approach through assignments.